Mid- to late-Holocene analysis of the influence of the La Plata River plume on the southwestern Atlantic shelf: A paleoenvironmental reconstruction based on lipid biomarkers and benthic foraminifera - Bicego, Marcia C; Santos, Felipe Rodrigues (PANGAEA, 2023)
The coupled results of sedimentological, molecular, and microfossil proxies were used to determine the paleoclimatic and paleoceanographic variations as well as identify the sediment transport pathways along the last c.a. 6,300 years in a sedimentary record collected on the inner shelf of the Southwestern Atlantic Ocean. Applied methods include the analyses of n-alkanes, n-alkanols, alkenones, and benthic foraminifera enabling a more complete environmental perspective of the La Plata River plume influence on the Southwestern Atlantic Shelf, regarding the relationship between climate, productivity, as well as hydrodynamic. Variations in marine productivity, lipid biomarkers of terrestrial plants, diagnostic geochemical indices, and sea surface temperature point to three phases within the core. These phases suggest the influence of synchronized variations in sea level, precipitation over the Paraná River drainage basin, and the northward displacement of the PPW by the BCC, transporting sediments from southern areas to the core 7606 region.
Keywords: Benthic foraminifera; La Plata River; lipid biomarkers; Paleotemperature; southern Brazil